2011
DOI: 10.1111/j.1469-8749.2011.04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified constraint-induced therapy for children with hemiplegic cerebral palsy: a randomized trial

Abstract: Aim  Conventional constraint‐based therapies are intensive and demanding to implement, particularly for children. Modified forms of constraint‐based therapies that are family‐centred may be more acceptable and feasible for families of children with cerebral palsy (CP)‐but require rigorous evaluation using randomized trials. The aim of this study was to determine the effects of modified constraint‐induced therapy compared with intensive occupational therapy on activities of daily living and upper limb outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
167
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(170 citation statements)
references
References 24 publications
2
167
1
Order By: Relevance
“…Thirteen types of UL interventions and numbers of participants were identified: NDT (2 studies; n = 122), 12,13 intramuscular injections of BoNT-A and OT (11 studies; n = 322), [14][15][16][17][18][19][20][21][22][23][24] cCIMT (3 studies; n = 56), 6,[25][26][27][28] mCIMT (15 studies; n = 578), 7,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] hybrid model (mCIMT and bimanual training; 2 studies; n = 68), 8,9 forced-use therapy (2 studies; n = 54), 48,49 HABIT (1 study; n = 20), 50 OT home programs (1 study; n = 35), 51 UL lycra splints (1 study; n = 16), 52 contextfocused therapy (1 study; n = 128), 53 mirror box therapy (1 study; n = 10), 54 acupuncture combined with OT (1 study; n = 75), …”
Section: Description Of Studiesmentioning
confidence: 99%
“…Thirteen types of UL interventions and numbers of participants were identified: NDT (2 studies; n = 122), 12,13 intramuscular injections of BoNT-A and OT (11 studies; n = 322), [14][15][16][17][18][19][20][21][22][23][24] cCIMT (3 studies; n = 56), 6,[25][26][27][28] mCIMT (15 studies; n = 578), 7,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] hybrid model (mCIMT and bimanual training; 2 studies; n = 68), 8,9 forced-use therapy (2 studies; n = 54), 48,49 HABIT (1 study; n = 20), 50 OT home programs (1 study; n = 35), 51 UL lycra splints (1 study; n = 16), 52 contextfocused therapy (1 study; n = 128), 53 mirror box therapy (1 study; n = 10), 54 acupuncture combined with OT (1 study; n = 75), …”
Section: Description Of Studiesmentioning
confidence: 99%
“…CIMT was not employed in its classic form and was modified with respect to the constraint method, duration of constraint (days or weeks), type and duration of therapy, intervention setting (home, school or clinic) and intervention provider (therapist, parent or teacher). The first significant variant was the method employed to constrain the unaffected limb, for which a range of techniques was used, such as a mitt 21,22,[24][25][26]28 , sling [17][18][19][20] , cast 27 and splint…”
Section: Discussionmentioning
confidence: 99%
“…Wallen M et al 28 Significant improvements in post-intervention "satisfaction" and "performance" (COPM) in both groups…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 There are several studies reviewed by Sakzewski et al in which CIMT was delivered in the home. 15,16 Training was implemented in these studies adhering to the guidelines of Novak et al, 17 but no use of the transfer package was reported. Thus, even though training was done in the home, systematic steps were not reported to have been taken to integrate use of the more-affected arm into daily life activities, which the transfer package accomplishes by a variety of means.…”
mentioning
confidence: 99%